Shear Bond Strength of Orthodontic Brackets Bonded with a Self-Adhering Composite in Dry and Saliva-Contaminated Conditions - Nastaran Sharifi; Azadeh Zakerzadeh; Zahra Mohammadi; Sepideh Arab; Fatemeh Vafadoost (Tehran University of Medical Sciences, 2022)
Objectives: The purpose of this study was to evaluate the effect of saliva contamination on shear bond strength (SBS) of orthodontic brackets bonded by a self-adhering composite compared with a conventional adhesive. Materials and Methods: This in vitro, experimental study investigated 40 human premolars. The teeth were randomly divided into four groups based on the adhesive type and bonding condition: (I) Vertise Flow composite without saliva contamination (VF), (II) Vertise Flow composite with saliva contamination (VF/S), (III) Transbond XT composite without saliva contamination (TXT), and (IV) Transbond XT composite with saliva contamination (TXT/S). After the preparation step, brackets were bonded to the buccal surface of the teeth, and samples were mounted in acrylic blocks, incubated at 37°C for 24 hours, and underwent thermocycling between 5- 55°C. Next, the SBS was measured by a universal testing machine. Data were analyzed by ANOVA and Tukey's test.  P<0.05 was considered statistically significant. Results: ANOVA showed a significant difference in SBS among the groups (P<0.001). The highest SBS was achieved in the TXT group (26.63±9.09 MPa), followed by TXT/S (13.69±4.23 MPa), VF/S (3.68±1.49 MPa), and VF (3.04±1.73 MPa). Conclusion: Saliva contamination did not have a significant effect on SBS of brackets bonded with Vertise Flow. However, it did not provide acceptable bond strength for orthodontic bracket bonding in the clinical setting.